P848 Risk of Orthorexia Nervosa in Patients with Inflammatory Bowel Disease: A Link with Eating Disorders?. (30th January 2023) - Di Giorgio, F M; Modica, S P; Ciminnisi, S; Saladino, M; Muscarella, S; Melatti, P; Brinch, D; Petta, S; Cappello, M
Abstract: Background: Self-imposed food restrictions are common in patients with inflammatory bowel disease (IBD) because oftheir erroneous belief of the role of food in disease worsening and, recently, eating disorders have alsobeen described. Orthorexia nervosa is characterized by the obsession of eating healthy and natural foods.Only a few studies have assessed orthorexia in patients with digestive disease and there are no studies inIBD. The aim of this study is to assess the risk of orthorexia in patients with IBD. Methods: 158 consecutive subjects were prospectively recruited from February to October 2022 in a tertiary referralcenter: 113 patients with IBD and 45 healthy controls. The cohort of IBD patients consisted of 74 patientson biologic drugs, 28 patients on conventional therapy, and 12 patients admitted to the ward for diseaseflares. Demographic and clinical data were collected, and the ORTO-15 questionnaire, validated by Doniniet al., was used to assess the risk of orthorexia. Results: Patients with IBD had a prevalence of orthorexia of 77%, significantly higher than the 47% observed in thecontrol group (p <0.001). No statistically significant differences between patients with and without risk oforthorexia in relation to age (p=0.66), gender (p=0.37), marital status (p=0.78), educational status (p=0.88), and occupation (p=0.64) were found, although a nonsignificant trend could be observed for a lower BMI inpatients with risk of orthorexia compared with those without orthorexia (mean BMI 26.7 VS 25 kg/m2, p=0.12). The prevalence of orthorexia did not differ in relation to the diagnosis of UC or CD (p=0.98), nor tothe duration (p=0.75), the type of biological or conventional therapy (p=0.42), disease activity as measuredby Mayo score/HBI (p=0.47), and the presence of ostomy (p=0.33). The only statistically significantdifference observed concerned the history of previous surgery for IBD in patients with orthorexia (19.5percent), versus 3.8 percent in patients without orthorexia (p=0.05). Conclusion: Our study showed that most patients with IBD has a risk of orthorexia and that this is associated with alower BMI and a history of previous surgery for IBD. Further research is warranted to evaluate the clinicalimpact of orthorexia in patients with IBD and its relationship with the avoidant restrictive food intakedisorder (ARFID) or other eating disorder. Evidence based counselling by a qualified dietician is stronglywarranted in IBD clinics.